Electrochemical Detection of Triglycerides Based on an Enzymatic Reaction and Electrocatalytic Oxidation with Nortropine‐N‐oxyl. Issue 4 (10th January 2019) - Ono, Tetsuya; Sato, Katsuhiko; Sasano, Yusuke; Yoshida, Kentaro; Dairaku, Takenori; Iwabuchi, Yoshiharu; Kashiwagi, Yoshitomo
Abstract: This work investigated a simple triglycerides (TGs) detection method combining an enzymatic reaction, using only lipase, and the electrocatalytic oxidation of glycerol with nortropine‐ N ‐oxyl (NNO). Tributyrin was employed as a model TG. In this method, TGs are degraded by lipase to glycerol and fatty acids, after which the glycerol reacts with NNO. Preliminary cyclic voltammetry trials demonstrated that the anodic peak current increased along with the glycerol concentration, giving currents of 53.2 and 97.3 μA (at +0.6 V vs . Ag/AgCl) in response to 10 and 100 mM glycerol, respectively. Amperometry confirmed the same response during constant potential electrolysis at+0.6 V vs . Ag/AgCl. This behavior was also observed in a system incorporating tributyrin and lipase, with increases in current proportional to the tributyrin concentration over the range of 0.1 to 10 mM. Abstract :